Opening Educational Practices in Scotland (OEPS) - Pete Cannell; Anna Page; Ronald Macintyre (Journal of Interactive Media in Education, 2016)
OEPS is a cross-sector project led by the Open University in Scotland (OUiS) and funded by the Scottish Funding Council. The project began in late spring 2014 and runs until the end of July 2017. It has its origins in OER projects carried out by the OUiS over the preceding four years. In most cases these involved close partnership between the university and other organisations that would not normally be involved in the creation of educational materials. OEPS aims to build on these approaches, and on other valuable experience from across the Scottish sector, to increase the use of open licensed resources in Scotland, develop better understanding of good open educational practice and support widening participation and transitions. The project is multi-stranded, involving a wide range of partners in development work. Integral to the project methodology is a process of embedded research and evaluation aimed at understanding and evidencing good practice. In this paper we share the progress of the project to date and highlight some of the questions and issues that are emerging.